CpPEt2As4—An Organic‐Substituted As4 Butterfly Compound. Issue 50 (15th November 2016) - Heinl, Sebastian; Balázs, Gábor; Stauber, Andreas; Scheer, Manfred
Abstract: Cp PEt 2 As4 (Cp PEt =C5 (4‐EtC6 H4 )5 ) (1 ) is synthesized by the reaction of Cp PEt. radicals with yellow arsenic (As4 ). In solution an equilibrium of the starting materials and the product is found. However, 1 can be isolated and stored in the solid state without decomposition. As4 can be easily released from1 under thermal or photochemical conditions. From powder samples of Cp PEt 2 As4, yellow arsenic can be sublimed under rather mild conditions ( T =125 °C). A similar behavior for the P4 ‐releasing agent was determined for the related phosphorus compound Cp BIG 2 P4 (2 ; Cp BIG =C5 (4‐nBuC6 H4 )5 ). DFT calculations show the importance of dispersion forces for the stability of the products. Abstract : As you like it : As4 butterfly compounds are rare and even unknown with organic substituents. The first organo‐derivative Cp PEt 2 As4 (see structure; Cp PEt =C5 (4‐EtC6 H4 )5 ) is prepared and the liberation of yellow arsenic from it is demonstrated in solution and in the solid state. Similar results were found for the related P4 butterfly molecule Cp BIG 2 P4 (Cp BIG =C5 (4‐ n BuC6 H4 )5 ).